Distribution of Vibrio parahaemolyticus in pacific white shrimp Litopenaeus vannamei through immersion as a natural infection model - Sari Anggraeni, Sukma; Sukenda; Nuryati, Sri; Wahjuningrum, Dinamella (Indonesian Society of Scientific Aquaculture (ISSA), 2024)
Vibrio parahaemolyticus is a pathogenic bacterium that indusces mortality is pacific white shrimp. This study aimed to analyze the distribution of V. parahaeomyticus in shrimp through immersion and evaluate, polymerase chain reaction, histopathology, and immune response. The study employed two treatments with four replicates each. Shrimp were infected through immersion with V. parahaemolyticus at a concentration of 107 CFU/mL for 30 minutes, followed by transferring the shrimp to a rearing container. Gill, hepatopancreas, gut, and hemolymph samples were collected at 6, 12, and 24 hours post-infection. Infected shrimp exhibited clinical symptoms such as a pale body and hepatopancreas, along with empty gut. Shrimp mortality reached 97.08%, while no mortality occurred in the control grouph. The abundance of V. parahaemolyticus in organs exceeded 105 CFU/mL. Histopathological examination revealed mild, moderate, and severe damage. PCR confirmation tests at 12 and 24 hours yielded positive results, with a DNA band at 230 bp. Immune responses, including total hemocytes, phagocytic activity, phenoloxidase, and respiratory burst, demonstrated significantly different results (P<0.05). It was concluded that the distribution of V. parahaemolyticus in the shrimp body, specifically in the gills, hepatopancreas, and gut, exceed 105 CFU/mL, as confirmed by a 230 bp DNA band in the PCR test. Tissue damage, manifested as lesions and necrosis, occurred in the gills, hepatopancreas, and gut. Additionally, the imun response of Vibrio-infected shrimp was found to be lower than that of uninfected shrimp (negative control). Keywords: distribution, immersion, Litopenaeus vannamei, Vibrio parahaemolyticus ABSTRAK Vibrio parahaemolyticus adalah bakteri patogen yang menyebabkan kematian pada udang vaname. Penelitian ini bertujuan menganalisis distribusi V. parahaemolyticus pada udang melalui perendaman serta kerusakan yang ditimbulkan melalui pengamatan gejala klinis, angka lempeng total bakteri, polymerase chain reaction, histopatologi dan respons imun. Penelitian menggunakan dua perlakuan dan empat ulangan. Udang diinfeksi melalui perendaman menggunakan V. parahaemolyticus 107 CFU/mL selama 30 menit, kemudian udang dipindah pada wadah pemeliharaan. Pengambilan organ insang, hepatopankreas, usus dan hemolim dilakukan pada jam ke-6, 12, dan 24 pascainfeksi. Udang terinfeksi memiliki gejala klinis seperti tubuh dan hepatopankreas pucat, usus kosong. Mortalitas udang mencapai 97.08% dan tidak ada kematian pada udang kontrol. Kelimpahan V. parahaemolyticus pada organ lebih dari 105 CFU/mL. Pengamatan histopatologi menunjukkan kerusakan ringan, sedang, hingga parah. Uji konfirmasi PCR jam ke-12 dan ke-24 menunjukkan hasil positif pada 230 bp. Respons imun seperti total hemosit, aktivitas fagositik, phenoloxidase, respiratory burst menujukkan hasil yang berbeda nyata (P<0.05). Disimpulkan bahwa distribusi V. parahaemolyticus di dalam tubuh udang pada terdapat pada insang, hepatopankreas dan usus lebih dari 105 CFU/mL dan terkonfirmasi uji PCR pada pita DNA 230 bp. Kerusakan jaringan seperti lesi dan nekrosis terjadi pada insang, hepatopankreas, dan usus. Respons imun udang yang terinfeksi Vibrio lebih rendah dibandingkan udang yang tidak terinfeksi (kontrol negatif). Kata kunci: distribusi, Litopenaeus vannamei, perendaman, Vibrio parahaemolyticus